2012
DOI: 10.1371/journal.pone.0041439
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic Cardiac Remodeling Induced by Taurine Deficiency in Wistar Rats

Abstract: IntroductionMicronutrient deficiency is observed in heart failure patients. Taurine, for example, represents 50% of total free amino acids in the heart, and in vivo studies have linked taurine deficiency with cardiomyopathy.MethodsThirty-four male Wistar rats (body weight = 100 g) were weighed and randomly assigned to one of two groups: Control (C) or taurine-deficient (T (-)). Beta-alanine at a concentration of 3% was added to the animals’ water to induce taurine deficiency in the T (-) group. On day 30, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Tau has been reported to have a wide developmental potential and cytoprotective functions in skeletal muscle where it is delivered by Tau transporter (Tau T) [ 45 ]. Indeed in TauT-knockout rodents, several cardiac and skeletal muscle alterations occurred [ 46 , 47 ] while Tau T expression was effective against dexamethasone-induced atrophy in vitro [ 48 ]. Tau was able to prevent oxidative damage, ER stress, and apoptosis in cardiomyocytes [ 49 , 50 ] and we recently reported that Tau rescued CisPt apoptosis in renal cells by inducing autophagy and limiting ER stress [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tau has been reported to have a wide developmental potential and cytoprotective functions in skeletal muscle where it is delivered by Tau transporter (Tau T) [ 45 ]. Indeed in TauT-knockout rodents, several cardiac and skeletal muscle alterations occurred [ 46 , 47 ] while Tau T expression was effective against dexamethasone-induced atrophy in vitro [ 48 ]. Tau was able to prevent oxidative damage, ER stress, and apoptosis in cardiomyocytes [ 49 , 50 ] and we recently reported that Tau rescued CisPt apoptosis in renal cells by inducing autophagy and limiting ER stress [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pharmacological inhibition of taurine transport using β-alanine or GES in both in vitro and in vivo studies resulted in significant pathological conditions, which include atrophic cardiac remodeling [ 126 , 139 , 140 ], oxidative stress [ 141 , 142 ], increased apoptosis [ 143 ], mitochondrial defects [ 83 , 84 ] and altered cardiac cell morphology [ 144 ], as well as loss of retinal ganglion cells that lead to retinopathy [ 128 ]. All these studies clearly demonstrated the importance of taurine as a cytoprotective agent with multiple physiological functions.…”
Section: Taurine Biologymentioning
confidence: 99%
“…Taurine is a free amino acid which plays a fundamental role in the human body by absorbing fats, protecting the heart and acting as an antioxidant (Alzawqari et al, 2016;Catharino et al, 2011;Giles et al, 2012;Goron & Moinard, 2018;Heidari et al, 2016;Mele et al, 2019;Pansani et al, 2012;Pereira et al, 2012;Rai et al, 2016;Wen et al, 2019). Regarding toxicity, it is generally well accepted by the body, without any adverse physiological effects.…”
Section: Introductionmentioning
confidence: 99%